2000
DOI: 10.1021/jp002431+
|View full text |Cite
|
Sign up to set email alerts
|

Barrier to Methyl Internal Rotation of Cis- and Trans-2-Methylvinoxy Radicals in the X̃(2A‘ ‘) and B̃(2A‘ ‘) States:  Experiment and Theory

Abstract: The jet-cooled laser induced fluorescence spectrum of the B̃ ← X̃ electronic transition of 2-methylvinoxy radical is assigned as a superposition of contributions from noninteracting cis and trans isomers. The spectrum of the cis isomer is identified by comparison with ab initio electronic structure calculations; both theory and experiment clearly indicate that the methyl conformation changes from the X̃ state to the B̃ state. Fits of both hot and cold bands to a one-dimensional torsional model yield methyl rot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 42 publications
5
26
0
Order By: Relevance
“…8 is similar to those of the methylvinoxy radicals, which mainly consist of the progressions of methyl torsion levels. 20,21 Therefore, the band system starting at 21 354 cm −1 could be tentatively assigned to those originating from one or both of the 2-MVT radicals. A detailed analysis for the band system is in progress.…”
Section: G Spectra Of Other Isomersmentioning
confidence: 99%
See 1 more Smart Citation
“…8 is similar to those of the methylvinoxy radicals, which mainly consist of the progressions of methyl torsion levels. 20,21 Therefore, the band system starting at 21 354 cm −1 could be tentatively assigned to those originating from one or both of the 2-MVT radicals. A detailed analysis for the band system is in progress.…”
Section: G Spectra Of Other Isomersmentioning
confidence: 99%
“…11,12 It is interesting that the methyl substitution effect of CH 2 CHS on theB −X origin position is compared with that of the oxygen analog, the vinoxy radical. The origin band positions of the vinoxy and its methyl-substituted species have been experimentally determined, [19][20][21] as summarized in Table VIII. It is seen that the origin band of the 1-methylvinoxy radical shifts from that of the vinoxy radical by −1503 cm −1 , while the shifts of 2-methylvinoxy radicals are much smaller.…”
Section: Effect Of Methyl Substitution On the Origin Band Positionmentioning
confidence: 99%
“…Extensive laser induced fluorescence (LIF) studies between the radicalX andB states of the n-methylvinoxy radical have been performed by Weisshaar and co-workers. 20,32 The radicals were generated from mixtures of cis-and trans-ethyl-1-propenyl ether, CH 3 CH = CHOCH 2 CH 3 , ranging in composition from 4:1 to 1:4, though the same spectrum was observed for all mixtures. Two backbone vibrations were tentatively identified in the cisB state, and considerable additional structure was attributed to hindered rotation resulting from differing orientations of the methyl group in theX andB states.…”
Section: Fig 1 C S Isomers Of the N-methylvinoxy Radicalmentioning
confidence: 99%
“…The cis isomer was found to be slightly lower in energy than the trans isomer for both the anion (0.080 eV) and neutral (0.03 eV) ground states, in disagreement with their experimental assignment of a primarily trans anion photoelectron spectrum. Geometries and energies for theX andB states of cis-and trans-n-methylvinoxy radicals were calculated by Weisshaar and et al, 32 who found the cis isomer to be ∼0.020 eV lower in energy for both states. Their calculations identified the gauche orientation (see Fig.…”
Section: Fig 1 C S Isomers Of the N-methylvinoxy Radicalmentioning
confidence: 99%
See 1 more Smart Citation